MATERIALIZING SPIRIT OF PROTESTANTISM WITHIN THE HEGEMONY OF CATHOLIC CHRISTENDOM ON SHAW’S SAINT JOAN - M ANDHY NURMANSYAH, M.Hum. (Jurnal Humanitas)
A chronicle play written by English dramatis George Bernard Shaw in 1924 entitled Saint Joan is a complex and complete play. It does not only give us understanding about the history of France during the Hundred-Year War but give us also an insight of the struggle of a heroine namely Joan (Jean in French) against the superiority of corrupted people inside the church. As manifested in her actions during the war, Joan is teaching French on how they should fight against the English men under the name of God. By applying content analysis through the elements of the play particularly focused on the actions of the main character, Joan, this library research has proved that Joan’s actions cannot be judged as what Christian Christendom did. Instead of doing heresy Joan’s actions were the materialization of the spirit of Protestantism known and fought previously by Martin Luther, a protestant initiator from German. This research also prove that punishment given to Joan at the end of her life was a political judgment created by some ambitious people within the top hierarchy of catholic church in France at that time.